Psychoactive substances in Poland and Hungary — how to fight them (problem overview)? - Jóźwiak, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In view of the very serious social problem of designer drugs, which is growing with every passing day, we must take resolute and eﬀective action as quickly as possible. Undoubtedly, designer drugs have become one of the plagues of the 21st century. The choice of Poland and Hungary is not random, as both countries have one of the highest percentage intakes of legal highs in Europe. In both countries possessing and traﬃcking in designer drugs is punishable by criminal liability.
Keywords: narkotyki; prawo karne; dopalacze; substancje psychoaktywne; przestępstwo